Respuesta :
Answer:
3p²-7r²-5r²-11
Step-by-step explanation:
(5p²-4q²-72²-6)
- (2p²+3p²-2r²+5)=
3p²-7r²-5r²-11
Answer:
see below
Step-by-step explanation:
Let's sim[plify step-by-step.
5p²−4q²−7r²-6−(2p²+3q²−2r²+5)
Distribute the Negative Sign:
=5p²−4q²−7r²−6+−1(2p²+3q²−2r²+5)
=5p²+−4q²+−7r²+−6+−1(2p²)+−1(3q²)+−1(−2r ²)+(−1)(5)
=5p²+−4q²+−7r²+−6+−2p²+−3q²+2r²+−5
Combine Like Terms:
=5p²+−4q²+−7r²+−6+−2p²+−3q²+2r²+−5
=(5p²+−2²)+(−4q²+−3q²)+(−7r²+2r²)+(−6+−5)
=3p²+−7q²+−5r²+−11
Answer:
=3p²−7q²−5r²−11